Motion of spinning particles around dynamic phantom AdS black holes - M. Umair Shahzad; Sana Khalid; Ali Övgün (European Physical Journal C: Particles and Fields, 2023)
Abstract This work is devoted to discussing spinning particles’ motion in the surrounding dynamic phantom AdS Black hole (BH) with phantom scalar field k. The primary goal of this research is to differentiate between the effects of electric and magnetic charges on dynamic phantom AdS BH. The study analyzes the dependence of the innermost stable circular orbit (ISCO), responsible for interactions between charged particles and the external magnetic field, and observes the circular orbits of particles revolving around the compact object. It is also observed that as electric and magnetic charges increase, the ISCO radius decreases. Additionally, stability of orbit, Keplerian frequency, and harmonic oscillations of charged particles are also discussed. We also find the condition, electric and magnetic charges of the dynamic phantom AdS BH effect the energy of the center of mass with magnetized, electrically charged, and neutral particles due to the collision. Lastly, we discuss the accretion process and obtain generalized equations for the speed of sound $$c^2_{s}$$ c s 2 sec, 4-velocity u(r), energy density $$ρ (r)$$ ρ ( r ) and mass ( $${\dot{M}}$$ M ˙ ). We also plot these physical parameters against constant values of mass, electric and magnetic charges, and distinct values of state parameter $$ω $$ ω to study the accretion process. We observe that radial velocity and energy density of the fluid remain positive and negative, and the rate of change of mass is increased and decreased for stiff, dust, quintessence, and phantom-like fluid, respectively.